It's about practising the right kind of normals - Abdullah, Muhammad Faris (2020)
The whole world is impacted by the COVID19 pandemic. While it creates chaos, it also reveals lessons that we might not have realised otherwise. But, more importantly, whether we have learned from these lessons? COVID19 promotes new normals. We have been consistently told to keep our distance from one another and to wear face masks in public places, and to practice personal hygiene such as keeping hands clean and exercise cough and sneeze etiquette. However, are these the only extent of new normal post-COVID19? We should learn more from COVID19 episode, especially lessons regarding mental health, good values and environmental sustainability. These must also be the normals post-COVID19.